1976
DOI: 10.1007/bf02461527
|View full text |Cite
|
Sign up to set email alerts
|

The dorsum sellae in infancy and childhood

Abstract: Abslract. Evaluation of the dorsum sellae in infants and children is often difficult. Understanding its normal development and anatomy will help in the detection of pathologic states. The normal central concavity of the dorsum, normal pointing and tapering of the superior dorsum, variation in size and shape of the posterior clinoids, ossified dural bridging and a variable size of the dorsum occur at these ages. Changes associated with hydrocephalus, intrasellar and suprasellar turnouts in the early stage may m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The dorsum increases in size until puberty after which no significant change takes place. 7,14,15 Significant wide variations in the PCP in different individuals and even between the opposite sides of the same individual have been reported, such as fusion of the ACP and PCP through an ossified interclinoid ligament. 9,10 One study reported bilateral complete ossification of the interclinoid ligament in 6% of autopsy cases.…”
Section: Surgical Relevance Of the Pcpmentioning
confidence: 99%
“…The dorsum increases in size until puberty after which no significant change takes place. 7,14,15 Significant wide variations in the PCP in different individuals and even between the opposite sides of the same individual have been reported, such as fusion of the ACP and PCP through an ossified interclinoid ligament. 9,10 One study reported bilateral complete ossification of the interclinoid ligament in 6% of autopsy cases.…”
Section: Surgical Relevance Of the Pcpmentioning
confidence: 99%